Emissaries in early modern literature and culture : mediation, transmission, traffic, 1550-1700 - Charry, Brinda; Shahani, Gitanjali (Transculturalisms, 1400-1700., 2009)
With its emphasis on early modern emissaries and their role in England's expansionary ventures and cross-cultural encounters across the globe, this collection of essays takes the messenger figure as a focal point for the discussion of transnational exchange and intercourse in the sixteenth and seventeenth centuries. It sees the emissary as embodying the processes of representation and communication within the world of the text, itself an 'emissary' that strives to communicate and re-present certain perceptions of the 'real.' Drawing attention to the limits and licenses of communication, the e.